Mental health and well-being interventions in sport research, theory and practice - Breslin, Gavin; Leavey, Gerard 1957- (Routledge psychological interventions, 2019)
Mental Health and Well-being Interventions in Sport provides an indispensable guide for researchers and practitioners wanting to understand and implement sport-based intervention processes. This important book adopts an evidence based approach, discussing the context of the intervention, its design and implementation, and its evaluation and legacy. With cases on depression, eating disorders, and athletic burnout, the book is designed to provide practitioners, policy makers and researchers with a cutting-edge overview of the key issues involved in this burgeoning area, while also including cases on how sport itself has been used as a method to improve mental health. Written for newcomers and established practitioners alike, the text is an essential read for researchers and practitioners in better understanding the sport setting-based intervention processes through presenting current research, theory and practice, applicable in a variety of sports settings and context